Transit timing variations in the WASP-4 planetary system. Issue 3 (19th September 2019) - Southworth, John; Dominik, M; Jørgensen, U G; Andersen, M I; Bozza, V; Burgdorf, M J; D'Ago, G; Dib, S; Figuera Jaimes, R; Fujii, Y I; Gill, S; Haikala, L K; et al.
ABSTRACT: Transits in the planetary system WASP-4 were recently found to occur 80 s earlier than expected in observations from the TESS satellite. We present 22 new times of mid-transit that confirm the existence of transit timing variations, and are well fitted by a quadratic ephemeris with period decay d P /d t  = −9.2 ± 1.1 ms yr −1 . We rule out instrumental issues, stellar activity, and the Applegate mechanism as possible causes. The light-time effect is also not favoured due to the non-detection of changes in the systemic velocity. Orbital decay and apsidal precession are plausible but unproven. WASP-4 b is only the third hot Jupiter known to show transit timing variations to high confidence. We discuss a variety of observations of this and other planetary systems that would be useful in improving our understanding of WASP-4 in particular and orbital decay in general.